2015
DOI: 10.1021/jacs.5b06217
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Stoichiometric U–O Bond Scission in Uranyl Species Supported by Pyridine(diimine) Ligand Radicals

Abstract: Two uranium(VI) uranyl compounds, Cp*UO2((Mes)PDI(Me)) (3) and Cp*UO2((t)Bu-(Mes)PDI(Me)) (3-(t)Bu) (Cp* = 1,2,3,4,5-pentamethylcyclopentadienide; (Mes)PDI(Me) = 2,6-((Mes)N=CMe)2C5H3N; (t)Bu-(Mes)PDI(Me) = 2,6-((Mes)N=CMe)2-p-C(CH3)3C5H2N; Mes = 2,4,6-trimethylphenyl), have been synthesized by addition of N-methylmorpholine N-oxide to trianionic pyridine(diimine) uranium(IV) precursors, Cp*U((Mes)PDI(Me))(THF) (1), Cp*U((Mes)PDI(Me))(HMPA) (1-HMPA), and Cp*U((t)Bu-(Mes)PDI(Me))(THF) (1-(t)Bu). These uranyl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 61 publications
5
90
0
Order By: Relevance
“…However, relativistic effects dictate that uranium has more chemically active 6d and 5f orbitals, which leads to increased orbital overlap and covalency in U−E multiple bonds. Uranium–oxo complexes have been studied extensively, particularly in the context of environmental transport and waste remediation efforts . The study of U−N multiple bonding is more limited, although it has recently achieved milestone discoveries in the isolation of the first examples of terminal molecular uranium nitride, terminal parent imido, and uranium tris(imido) moieties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, relativistic effects dictate that uranium has more chemically active 6d and 5f orbitals, which leads to increased orbital overlap and covalency in U−E multiple bonds. Uranium–oxo complexes have been studied extensively, particularly in the context of environmental transport and waste remediation efforts . The study of U−N multiple bonding is more limited, although it has recently achieved milestone discoveries in the isolation of the first examples of terminal molecular uranium nitride, terminal parent imido, and uranium tris(imido) moieties .…”
Section: Introductionmentioning
confidence: 99%
“…Uranium-oxo complexes have been studied extensively,p articularly in the context of environmental transport and waste remediation efforts. [4][5][6][7][8] The studyo fU À Nm ultiple bondingi sm ore limited, although it has recently achieved milestone discoveries in the isolation of the first exampleso ft erminal molecular uranium nitride, [9][10][11] terminal parenti mido, [12] and uranium tris(imido) moieties. [13,14] Presently,t here are an umber of high-valent uraniumb is(imido) complexes reported in the literature, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] as well as uranium mono(imido)c omplexes in the uranium + 4, [24][25][26][27][28][29][30][31][32][33][34][35] + 5, [36][37][38][42][43][44][45][46] and + 6…”
Section: Introductionmentioning
confidence: 99%
“…The structure showed that the uranium-nitrogen bonds have been deprotonated because the bond lengths are all similar now (U1-N1 = 2.307(6), U1-N2 = 2.316(6), U1-N3 = 2.302(6) Å), and all bond lengths show that the uranium-nitrogen bonds are all anionic. The bond-distances found in Cp*U( t BuMes PDI Me )(THF), a compound made previously in our lab, showed three uranium-nitrogen bond distances slightly shorter than Cp*U(RITA)(LiCl(THF) 2 ), but also with anionic nitrogen atoms (U1-N1 = 2.293(2), U1-N2 = 2.204(3), U1-N3 = 2.293(2) Å) (Kiernicki, Cladis, Fanwick, Zeller, & Bart, 2015). A new LiCl(THF) 2 complex formed in place of the H atom in Cp*U(RITA) (LiCl(THF) 2 ), which bridges the uranium and nitrogen.…”
mentioning
confidence: 56%
“…In addition, the active catalystofHCOOHdehy- www.chemeurj.org drogenation is the aluminumc omplex with three HCOO À units and at wice-protonated PDI ligand (complex 7). In the catalytic cycle of formic acid dehydrogenation, 7 undergoes b-hydride elimination( the rate-determinings tep) via an unconventional transition state, followed by formation of the Al-H complex (9), which assists HCOOH dehydrogenation. The computational results reveal the important role of aluminum-ligand cooperation in the HCOOH dehydrogenation reaction, as it promotes the OÀHb ond activation of HCOOH to generate the reactive complexa st he active catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…on bis(imino)pyridine (PDI for short) iron/ cobalt complex catalyzed olefin polymerization, [2] and the precedent report of the redox non-innocent properties of the PDI ligand by Wieghardt et al, [3] the redox non-innocent PDI ligand has attracted extensive attention. [4] Various PDI-based metal complexes, including iridium, [5] nickel, [6] tin, [7] vanadium, [8] uranium, [9] germanium, [10] and molybdenum [11] have been reported.B oth experimental (e.g.,m agnetic studies,s pectroscopic analysis) andt heoretical techniques (e.g.,D FT calculations) have been applied to characterizea nd understand the properties of bis(imino)pyridylo rganometallic complexes. Based on these efforts, bis(imino)pyridylm etal complex mediated organic reactions have made great progress.…”
Section: Introductionmentioning
confidence: 99%